2020
DOI: 10.1016/j.msea.2020.139592
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and mechanical investigation of the near fusion boundary region in thermally aged 18MND5 / alloy 52 narrow-gap dissimilar metal weld

Abstract: Detailed characterization of the near fusion-boundary region of 18MND5 / Alloy 52 dissimilar metal weld joints was performed to investigate the effect of thermal aging on the microstructure and mechanical properties and to quantify the diffusion of carbon into the weld metal. It was shown that the microstructural features of dissimilar metal welds, such as the size of the partially mixed zone in the weld and the adjacency to microsegregations in the low-alloy steel have an effect on the peak carbon concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…Wang et al [15] characterized the crystal structures of Cr23C6 carbides and alloy 52M weld metal and found that both precipitate and matrix have FCC crystal structure, and that the lattice constant of Cr23C6 is 3 times the size of that of alloy 52M, in agreement with prior investigations on the crystal structure of Cr23C6 [16]. The presence of chromium-rich carbide precipitates isostructural to Cr23C6 was qualitatively demonstrated in the present DMW [2].…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Wang et al [15] characterized the crystal structures of Cr23C6 carbides and alloy 52M weld metal and found that both precipitate and matrix have FCC crystal structure, and that the lattice constant of Cr23C6 is 3 times the size of that of alloy 52M, in agreement with prior investigations on the crystal structure of Cr23C6 [16]. The presence of chromium-rich carbide precipitates isostructural to Cr23C6 was qualitatively demonstrated in the present DMW [2].…”
Section: Introductionsupporting
confidence: 88%
“…Accordingly, many authors have reported an increase in the micro-hardness in weld metal next to the fusion boundary [5][6][7][8][9][10], which is related to this carbon migration. The magnitude of carbon transport during aging in service conditions was investigated in the present weld and was shown to be strongly correlated to changes in the local mechanical properties [2].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations